An estimate of the prevalence of dementia in Africa: a systematic analysis - Rhiannon George-Carey; Davies Adeloye; Kit Yee Chan; Abigail Paul; Ivana Kolcˇić; Harry Campbell; Igor Rudan (Edinburgh University Global Health Society, 2012)
The burden of non-communicable diseases is growing, particularly in developing countries. The greatest economic burden is due to dementia, the prevalence of which is rising with increasing longevity. In Africa, where the rate of increase of elderly persons is the fastest in the world, dementia is normally dismissed as a part of normal ageing. The lack of awareness means that many patients are suffering undiagnosed. This review aims to assess the information on the prevalence of dementia in Africa in order to estimate the current burden.